Studi Literatur Status Resistensi Aedes sp. Terhadap Larvasida di Indonesia - Jefriyono Christian Kandi; Julianty Almet; Nemay A Ndaong (Jurnal Veteriner Nusantara, 2023)
Aedes sp. is the main vector of dengue hemorrhagic fever, which consists of Ae. Aegypti and Ae. albopictus. DHF cases in Indonesia always fluctuate every year, in 2019 there were 138,127 cases and 919 deaths. The population and habitat of the dengue vector is important information in the control and prevention strategy both naturally and chemically by using insecticides. Common insecticides that are often used are divided into 4 groups, namely carbamates, organophosphates, organochlorines, and pyrethroids. The use of insecticides in inappropriate doses for a long time can lead to resistance. This study aims to determine the resistance status of Aedes sp. against insecticides used in Indonesia. This research is a type of library research using a minimum of 50 literatures, preferably those published in the last ten years. The source of the literature is taken based on the relationship or relationship with the title of the literature study that will be studied. The library search was obtained from Google Scholar with the help of the Mendeley application and analyzed descriptively. The results showed that there were 15 types of insecticides from four classes of insecticides that were no longer effective in controlling dengue vectors in Indonesia, such as: Carbamates (bendiocarb 3.45%), Organophosphates (bromophos 1.72%, fention 1.72%, clopyrifos 1.72%, lamdasihalothrin 1.72 %, malation 20.69%, temefos 18.97%), Organochlorines (DDT 1.72%, dieldrin 1.72%), and Pyrethroids (D-alletrin 3.45%, deltamethrin 6.90%, lamdacyhalothrin 3.45%, metofluthrin 1.72%, permethrin 18.97%, cypermethrin 10.34% , transfluthrin 1.72%. Of the 15 species, malation was the most common type of insecticide found, namely 20.69%, followed by temefos and permethrin each with 18.97%.